ENHANCE OUTPUT OF NATIONAL POLICIES THROUGH RECRUITMEN, SELECTION, AND COMPETENCE TO CHANGE OF NATIONAL CONDITION - Wiranto Wiranto (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This study explores the effects of recruitment, selection, competence and national policies to the changing conditions in Indonesia. 530 respondents from 25 provinces or 50 regencies/cities across Indonesia participated in questionnaire pools in the study. Data were processed using path analysis technique. Results reveal that the recruitment process by political parties, the selection process by the Election Commission, and the competence of the leader, have positive correlations to the policies and the outcomes. The study highlights that without any improvements in the recruitment, selection, competency of leaders, and policies, no changes could be made by the leaders. It implies that a redefinition and actualization of recruitment, selection, competence, and policies should be made to ensure the changes to take place. Keywords: change of national condition, actualization of recruitment, competencies, national policies.